2011
DOI: 10.1002/pssc.201001059
|View full text |Cite
|
Sign up to set email alerts
|

Dual temperature process for reduction in regrowth interfacial charge in AlGaN/GaN HEMTs grown on GaN substrates

Abstract: The effects of growth temperature and Mg compensation doping on the structural and electrical properties of AlGaN/AlN/GaN high electron mobility transistor (HEMTs) structures grown on low threading dislocation density bulk GaN substrates by metalorganic chemical vapor deposition were investigated. The background electron concentration in the regrown GaN was found to decrease from 1.5x1018 cm‐3 to 2x1016 cm‐3 as the growth temperature was reduced from 1100 °C to 950 °C. A dual temperature process was then emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…At present, it is believed that the reason for the increase of 2DEG density in the AlGaN/GaN HEMT structures grown on GaN substrates is related to Si impurities. 8,9,11,13) In this study, we observed a decrease of the 2DEG mobility due to an abnormal increase of the 2DEG density. The latter was caused by a donor with thermal ionization energy around 67.8 meV, the donor is not Si but N vacancy.…”
Section: Introductionsupporting
confidence: 50%
See 1 more Smart Citation
“…At present, it is believed that the reason for the increase of 2DEG density in the AlGaN/GaN HEMT structures grown on GaN substrates is related to Si impurities. 8,9,11,13) In this study, we observed a decrease of the 2DEG mobility due to an abnormal increase of the 2DEG density. The latter was caused by a donor with thermal ionization energy around 67.8 meV, the donor is not Si but N vacancy.…”
Section: Introductionsupporting
confidence: 50%
“…8) Eichfeld et al found that the number of redundant electrons could be reduced by introducing compensation doping and an AlN layer at the growth interface of the GaN substrate. 9) Generally, the GaN substrates easily adsorb donor impurities such as C, O, and Si from chemical-mechanical polishing processes and the atmospheric environment. However, Si impurities are more difficult to remove completely by substrate-cleaning methods such as chemical etching and in situ heat treatment than are C or O.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike n-type AlGaN, regrowth of p-type AlGaN may be very difficult in the presence of incidental silicon delta doping at the regrowth interface [8], but this issue does not appear to be fundamental. Various approaches are reported in the literature to suppress Si spikes [8], [9]. This article presents a 290 nm UV edge emitting LCI LD design using polarization charge matched quaternary QWBs and regrown Ohmic contacts.…”
Section: Introductionmentioning
confidence: 98%
“…In this paper, the device is fabricated on AlGaN/GaN epilayer grown by metal organic chemical vapor deposition (MOCVD) on hydride vapor phase epitaxy (HVPE) commercial free-standing gallium nitride (GaN) substrate. This structure presents the advantages of the direct growth of high crystalline quality GaN with threading dislocation density below 10 7 cm −2 [5,6]. The goal of this study is to demonstrate the high microwave power performance at 40 GHz of HEMTs on GaN substrate.…”
Section: Introductionmentioning
confidence: 99%